PENGARUH VARIASI PRODUK DAN CITA RASA TERHADAP KEPUTUSAN PEMBELIAN SEBLAK TEKWAN KUAH MERAH PADA KEDAI SEBLAK PRABUMULIH - Septiana, Indah; Robyardi, Erfan; Salmah, Ninin Non Ayu (Journal of Management Small and Medium Enterprises (SMEs), 2024)
The purpose of this research is to find out how the influence of product variations, taste, and purchasing decisions at Kedai Seblak Prabumulih. This is a survey research with two independent variables of product variation, taste, and the dependent variable of purchasing decision. Data collection by distributing questionnaires to 99 respondents at Kedai Seblak Prabumulih. The obtained data was applied to the classical assumption test consisting of the normality test, multicollinearity test, heteroscedasticity test, multiple regression analysis, coefficient of determination, and hypothesis testing consisting of t-test and F-test. The result showed that partially there was a significant effect between the product variation and the taste on purchasing decisions. There is a significant influence between product variations and taste simultaneously on purchasing decisions at Kedai Seblak Prabumulih. Keywords : Product Variation; Taste; Purchase Decision